EFEKTIFITAS PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN KONTEKSTUAL BERBASIS PAKEM - Ade Susanti (Pendidikan Matematika | STKIP YM Bangko, 2017)
Background of the mathematics learning process is still dominated by classes that focus on teachers as the main media of knowledge (teacher centered). The learning process has not been able to foster students' creativity and attractiveness in learning. This study aims to describe the use of contextual approaches in improving integer mathematics learning. Data retrieval is done by observation techniques for analysis of qualitative data and assessment of test results as an analysis of quantitative data. Data analysis techniques use simple statistics. The results of the study showed an increase in student activity in the learning process in class VII of SMP Negeri 28 Merangin. In percentage the average student learning outcomes from the initial test to the second cycle increased from 43.5% to 69.6% in the first cycle and 91.3% in the second cycle. This approach can be used as an alternative for teachers in learning mathematics. Keywords: contextual approach, PAKEM, learning, and learning outcomes